Seemingly neoplastic destructive lesion of maxillary sinus, eroding the bone and extending into skull base- Atypical Rhinoscleromaor Antroscleroma - Dr. Sunitha Shankaralingappa; Dr. Santhosh Shivaswamy (Tropical Journal of Pathology and Microbiology, 2018)
Rhinoscleroma (RS) is a chronic granulomatous infectious disease predominantly affecting the nose and upper respiratory tract caused by Klebsiella rhinoscleromatis (KR), a gram negative diplobacillus. In India, it is prevalent in Northern and central parts. Belinov, in 1932 proposed the term “scleromarespiratorium” as the disease process may involve not only the upper, but also lower respiratory pathways. A 35 year old male from South India, presented with mass in the right maxillary and ethmoid sinuses eroding the bone, extending into infratemporal fossa and skull base, clinically mimicking malignancy. Histopathological examination confirmed rhinoscleroma. Nasal cavity free, isolated ipsilateral involvement of sinusesmakes this case interesting and one among the few case reports reported in the past. Rhinoscleroma should be differentiated from other granulomatous conditions and neoplastic diseases like lymphoma & Sinonasal carcinoma. Correct diagnosis is very crucial as sinus-positive cases are linked with antibiotic resistance and early recurrence after medical treatment.